Scene da un "matrimonio". Performance, genere e identità a Napoli - Eugenio Zito (EtnoAntropologia, 2018)
In this paper, after having synthetically reconstructed the traditional role of the femminielli in Neapolitan society, intertwining linguistic analysis with historical, anthropological, literary and mythographic sources, and highlighting complex processes of molding and reshaping, I will focus on the singular ritual of “marriage”, by using visual material collected in the field during an ethnographic research carried out in Naples in 2010. Combining a perspective of diachronic analysis with a synchronic one, the deep cultural nature of the practices of construction of gender and of the social identity of such gender variant subjectivities is shown through the analysis of a still persistent traditional ritual device in a contemporary metropolitan context. Concepts as performance and gynomimetics are used for this analysis and the strong participation of the neighborhood community in their social life is highlighted.